Synthesis 2005: Changing the way we manage water for food, livelihoods, health and the environment - Harrington, Larry W.; Gichuki, Francis N.; Bouman, B.; Johnson, Nancy L.; Ringler, Claudia; Suganan, V. (CGIAR Challenge Program on Water and Food, 2006)
As befits a CGIAR Challenge Program , the CPWF has welcomed a wide range of stake holders and partners in accord with their ability to achieve program goals. Decision on research investments (project selection) have been based on a competitive grants in which proposal quality was evaluated by an interdependent external panel. The usual weakness of a competitive grants approach - lack of coherence in research agenda has been address by Basin Focal Projects and synthesis research.